Evaluation of the Results of China’s Fiscal Medical and Health Expenditure - Wang B; Wang X (Dove Medical Press, 2022)
Bin Wang,1 Xiuzhi Wang1,2 1School of Finance, Renmin University of China, Beijing, People's Republic of China; 2China Financial Policy Research Center (Renmin University of China), Beijing, People's Republic of ChinaCorrespondence: Xiuzhi Wang, Shool of Finance, Renmin University of China, No. 59 Zhongguancun Street, Haidian District, Beijing, 100872, People's Republic of China, Email wxiuzhi@ruc.edu.cnPurpose: To evaluate the resulting level of fiscal medical and health expenditure in China, and to provide the scientific basis for further improving fiscal medical and health service capacity in China.Patients and Methods: The data envelopment method and Gini coefficient method were used to analyze the efficiency and regional fairness of fiscal medical and health expenditure results by using the relevant provincial and municipal data of China from 2007 to 2019.Results: 1.Overall, from 2007 to 2019, the total expenditure continued to increase, the expenditure efficiency increased first and then decreased, and the expenditure fairness continued to improve. 2. From the perspective of subregions, there are apparent differences between regions in terms of total expenditure, expenditure efficiency, and expenditure fairness, showing a better situation in the central, western, northeast and a lower situation in the east.Conclusion: The overall level of fiscal medical and health expenditure in China shows an upward trend, but there is still much room for improvement. At the same time, there are pronounced regional differences, and the problems of efficiency and fairness coexist among regions. Therefore, in the future, we should increase medical and health investment and enhance the government's close attention; Improve the expenditure performance appraisal system; Formulate policies according to local conditions and avoid "one size fits all.".Keywords: fiscal medical and health expenditure, efficiency of expenditure results, fairness of expenditure results, regional differences, government attention